Morphological Features and Immunohistochemical Profiling of Male Breast Gynaecomastia; A Large Tissue Microarray Study - Prasad, Prakruthi; Bennett, Aneliese; Speirs, Val; Shaaban, Abeer M. (Frontiers in Oncology, 2022)
Introduction Gynaecomastia is the commonest male breast condition accounting for approximately 85% of male breast lesions. There is minimal information on the immunohistochemical profile of gynaecomastia. We aimed to comprehensively profile a large series of gynaecomastia samples for putative mammary diagnostic, predictive and prognostic markers. Methods A total of 156 samples, were histologically reviewed, assembled onto tissue microarrays, and stained for oestrogen receptors (ERα, ERβ1, ERß2), progesterone receptors (total PR, PRα), androgen receptor (AR), basal & luminal cytokeratins (CK5/6, CK14, CK8/18) and the proliferation marker Ki67. Relevant cut offs for marker positivity were defined based on existing literature: AR (10%), ERα and PR (Allred score >3/8), ERß (10% and 20%), cytokeratins (10%) and Ki67 (10% and 20%). Results 108 samples from 86 patients aged 13-75 years were available for immunohistochemical assessment. 73.1% of the lesions were AR positive, compared to 99% for ERα and 100% for both ERß1 and ERß2. 98% of samples were positive for total PR and 97.1% for PRα. 69.8% expressed CK5/6 whilst 57% were CK14 positive. A tri-layered pattern of cytokeratin expression was also observed. Ki67 positivity was low with 17.1% and 6.7% classified as Ki67 positive using 10% and 20% cut off values respectively. A significant negative correlation was found between ERα expression and patient age (rs = -0.221, p=0.023). Bivariate correlations were produced, and comparisons made with previously published data regarding the immunohistochemical status in normal female breast tissue, proliferative and neoplastic breast diseases of the female and male breast. Conclusions Hormone receptors, including oestrogen receptor α and ß isoforms as well as androgen receptors were abundantly expressed within the intraductal luminal hyperplastic epithelium in gynaecomastia supporting the hormonal role in the pathogenesis and treatment. ERα, ERβ1 and ERβ2 were expressed in a higher proportion of cells compared with their expression in the female breast benign lesions which further characterises gynaecomastia biology. The identification of a low Ki67 proliferative index and the mixed cytokeratin profile in gynaecomastia differentiates this benign condition from male breast cancer. Therefore, Ki67 and cytokeratins can help in the differential diagnosis from histological mimics in the routine diagnostic work up.